Legal Protection of Registered Mark Owner in Indonesian - Abdul Hakim (BIRCU, 2020)
Before the laws of mark well-known in Indonesia, the Indonesian people were happy to participate their creativity in being invited by others, feeling proud of the copyrighted work was finally followed by many people, but following the development of the era as it is now imitating other people's work is used as business object and profitable itself, so that in accordance with its development the owner is considered disadvantaged by the act of imitating his work because it involves business interests and/or profit and gain. Research is a basic tool in the development of science and technology. This research aims to reveal the truth systematically, methodologically, and consistently through the process of research analysis and construction of data that has been collected and processed. The problem in this research is the problem of protection of registered mark owners in Indonesia. The result of this research is mark rights are an important part of marks, therefore mark rights are privileges for their owners, brands are important in the marketing and advertising world, and therefore specifically related to the deadline for protection of registered marks for 10 years, the time limit which is deemed short can be extended, the replacement in accordance with the registered mark is actually used in goods/services and they needed and/or sold and is still on the market and is still distributed.